N-{4-[(3,4-Dimethylphenyl)(ethyl)sulfamoyl]phenyl}-N-ethylacetamide - John, P.; Khizar, S.; Khan, I.U.; Sharif, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
When viewed down the central S center dot center dot center dot N axis of the title compound, C20H26N2O3S, it is apparent that the molecule adopts a gauche conformation with all O atoms lying to one side of the central benzene ring; the carbonyl O atom is directed away from the central ring and the N-bound ethyl groups lie to one side of the molecule. Supramolecular helical chains aligned along the b axis and sustained by C-H center dot center dot center dot O contacts feature in the crystal packing. These are consolidated in the three-dimensional structure by C-H center dot center dot center dot pi interactions.